Development of an Islamic Religious Education Curriculum Based on Character Education at Muhammadiyah 36 Medan Integrated Elementary School - Sipahutar, Romat Efendi (Education Achievement: Journal of Science and Research, 2023)
The education that is really needed at this time is education that can integrate character education with education that can optimize the development of all dimensions of children (cognitive, physical, social-emotional, creative and spiritual). Education with the development of Islamic education like this is oriented towards the formation of children as complete human beings. The quality of students becomes superior not only in the cognitive aspect, but also in their character. School becomes a forum for forming a person's thought patterns and behavior, which shape students' spiritual attitudes and social attitudes. In developing the religious education curriculum, character at the Muhammadiyah Integrated Elementary School strives to develop character formation programs supported by good communication between teachers and parents of students through class and school associations.